Relative importance of common bean attributes and variety demand in the drought areas of Kenya - Katungi, E; Sperling, L.; Karanja, D.; Farrow, Andrew; Beebe, Stephen E. (2011)
The work assessed the relative importance of production and consumption attributes of different wealth groups of households and tested the effect of attribute preference and that of other factors on common bean variety demand in the drought areas of Eastern Kenya. Variety demand was conceptualized within the agricultural household framework and attributes incorporated in the model according to the Lancaster (1966) consumer theory. Empirical analysis was based on primary data collected from two districts of Eastern Kenya using the stated preference and revealed preference methods. A factor analysis was used to cluster a set of common bean variety attributes that were highly preferred by households into those related to consumption flavour and yield related characteristics. The effect of consumption and production attributes and those of other factors were estimated through applying ordinary least squares regression. Important implications for breeding priority setting in short term and long term as well as variety dissemination were drawn from the results. It was found that farmers preferred many common bean attributes and that four production attributes and one consumption attribute were rated important with an average rating of more than 2.5 on a three-point scale. This implies that genetic improvement that incorporates both desirable production and consumption traits would enhance the welfare of the people, especially the poorer households. Therefore, the breeding effort should target varieties with superior production attributes that are compatible with farmers consumption preferences.